PENGARUH SISTEM PENGELOLAAN AIR DAN VARIETAS TERHADAP HASIL PADI DAN EMISI GAS RUMAH KACA DI LAHAN TADAH HUJAN - Ali Pramono; Terry Ayu Adriani; Prihasto Setyanto (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
Rice field is an important role in sustainable national food security, rice production contributes to greenhouse gas emissions significantly, especially methane (Ch4). Some of these efforts to reduce GHG emissions in the paddy field has been done, such as water and fertilizer management, using low methane emission of rice varieties. The main objective of this study was to determine the effect of water management systems and rice varieties on grain yield and GHG emissions. The study was conducted at the Experimental Research Station of IAERI, Pati, Central Java in March to June 2016. The study design was a split plot with the factor I water management (A1 = Flooded 5 cm and A2 = Alternate Wetting and Drying / AWD), factor II rice varieties (V1 = Ciherang, V2 = Inpari 30, V3 = IPB3S), and replicated 3 times. GHG measurement was conducted using a closed chamber. The parameters were observed mainly CH4 and N2O fluxes, Eh and pH, water level surface, plant height and tiller number, grain and yield components. The results showed that the highest grain yields was A2V1 -1 treatment (AWD and Ciherang variety) amounted to 3.26 tons ha . The lowest of CH4 emissions was A2V1 treatment (AWD and Ciherang variety). N2O emissions produced the lowest in treatment A2V3 (AWD and IPB3S variety). The highest of GHG emissions was A1V3 treatment (continuous flooding and IPB3S variety). The lowest of GHG emissions was A2V1 treatment (AWD and Ciherang variety). The lowest emissions index was A2V2 treatment (AWD and Inpari 30 variety). AWD treatment could reduce GHG emissions of Ciherang, Inpari 30 and IPB3S rice varieties by 42%, 46%, and 30% compared to continuous flooding, respectively.